Preliminary Study of Juridical Aspects of Renewable Energy Draft Law In Indonesia: An Academic Perspectives - Rosyid Ridlo Al Hakim; Eko Ariyanto; Yanuar Zulardiansyah Arief; Aming Sungkowo; Trikolas Trikolas (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2022)
AbstractEnergy is an absolute necessity used in the survival of daily human life. The need for electrical energy in Indonesia continues to increase with economic growth and population increase. Indonesia's electricity demand is projected to increase more than seven times to 1,611 TWh in 2050. Through Commission VII of the House of Representatives of the Republic of Indonesia (DPR RI), the Indonesian government is drafting a Renewable Energy (RE) Bill. This rule provided a more detailed and in-depth explanation of the rules in terms of developing New and Renewable Energy (NRE) in Indonesia. This study critically reviews the formal juridical or regulatory aspects of Indonesia's Renewable Energy law (called RUU-EBT). This writing methodology is based on a literature review and data collected from relevant regulations and proposes the conclusion from relevant and expected regulations.AbstrakEnergi merupakan kebutuhan mutlak yang digunakan dalam kelangsungan hidup manusia sehari-hari. Kebutuhan energi listrik di Indonesia terus meningkat sejalan dengan pertumbuhan ekonomi dan pertambahan jumlah penduduk. Kebutuhan listrik Indonesia diproyeksikan meningkat lebih dari 7 kali lipat menjadi 1.611 TWh pada tahun 2050. Pemerintah Indonesia melalui Komisi VII Dewan Perwakilan Rakyat Republik Indonesia (DPR RI) saat ini sedang menyusun RUU Energi Baru dan Terbarukan (EBT). Aturan ini dibuat untuk memberikan penjelasan yang lebih detail dan mendalam tentang aturan dalam hal pengembangan EBT di Indonesia. Kajian ini memberikan tinjauan kritis terhadap aspek yuridis formal atau regulasi dari undang-undang Energi Baru dan Terbarukan (disebut RUU-EBT) di Indonesia. Metodologi penulisan ini didasarkan pada tinjauan pustaka (review paper) yang berkaitan dengan tujuan studi ini, serta data yang dikumpulkan dari peraturan hukum yang relevan dan mengusulkan kesimpulan dari peraturan hukum yang relevan dan diharapkan.